A 1, 8-naphthalimide based small molecular acceptor for polymer solar cells with high open circuit voltage. Issue 27 (11th June 2015) - Zhang, Xuejuan; Zhang, Jicheng; Lu, Heng; Wu, Junyan; Li, Guangwu; Li, Cuihong; Li, Sihui; Bo, Zhishan
Abstract : A PCE of 2.01% with a V oc of 1.30 V was obtained from polymer solar cells based on a 1, 8-naphthalimide based small molecular acceptor, which was synthesized via direct C–H activation. Abstract : A novel small moleculeNI-T-NI with a thiophene core and two 1, 8-naphthalimide terminal groups was synthesized via direct C–H activation and used as the acceptor for polymer solar cells.NI-T-NI exhibits a good crystallinity and can form H-aggregates in the solid state.NI-T-NI has a rather high-lying LUMO level, which is beneficial for achieving a high V oc . In cooperation with a high-lying LUMO level polymerPCDTBT-C12, a PCE of 2.01% with a high V oc of 1.30 V has been achieved. As far as we know, a V oc of 1.30 V is the highest value reported for single junction organic solar cells. Our results have demonstrated that 1, 8-naphthalimide could be a useful building block for the synthesis of promising acceptor materials for polymer solar cells.